Resistance of Haemonchus contortus to rafoxanide in sheep - Santiago, Marco Aurélio M.; Costa, Ubiratã Cereser da; Benevenga, Sérgio Fauque; Macedo, Nei (Pesquisa Agropecuaria Brasileira, 2014)
A controlled anthelmintic test was carried out in experimentally infested sheep to verify the action of rafoxanide on an Haemonchus contortus strain labelled as a resistant one to the drug. This suspected resistant strain was obtained from the sheep breeded in a farm at Uruguaiana country, Rio Grande do Sul, Brazil. The drug produced no reduction when it was used in a dose of 7.5 mg/kg, but it produced a 50 percent reduction when used in a dose of 15 mg/kg.